The Effective Use of Storytelling to Encourage EFL Students' Participation and Interest in Speaking English - Sulastri Sulastri; Ratnawati Ratnawati; Andi Hudriati (ELT Worldwide: Journal of English Language Teaching, 2022)
The purpose of this research is to increase students' participation and enthusiasm in English speaking through story telling. The research examined the following components of speaking ability: pronunciation, grammar, vocabulary, fluency, and comprehension. Classroom action research was employed as the research approach. The subjects of this study were third semester students in the literary faculty for the academic year 2019/2020, a total of 30 participants. The data were gathered using a series of tests, an observation checklist, a questionnaire, and a video recording. It was assessed utilizing a descriptive test, an observation checklist, a questionnaire, and a video recording, as well as the mean score formula. The findings suggested that story telling elevated the participation and engagement of students speaking English in two cycles. The results of the analysis of the category of speaking skills or student participation indicated an improved performance in the average percentage of students who obtained a score of 55 very low with a percentage of 63.33 % and 0% in the very high category, the first cycle with a percentage of 13.33 % in the high category with a score of 80-89, and the second cycle with a percentage of 46.6 % who obtained a high score of 14. While the questionnaire data revealed the students' interests. These findings demonstrate that when a story telling model is used, participation and enthusiasm in speaking increased.